Penerapan Strategi Picture Word Inductive Model Guna Meningkatkan Hasil Belajar Dalam Menyusun Teks Deskriptif Berbahasa Inggris Bagi Siswa Kelas VII SMP - M. Natsir (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to improve the learning outcomes to write in English, especially in describing objects, people or certain places through learning Picture Picture Inductive Model strategy. Data collection is carried out simultaneously with observations during the action, while data analysis is carried out simultaneously at the time of reflection of action. Research using data analysis in the form of triangulation methods, shows the results that there is an increase in learning outcomes of students in learning English writing when using the PWIM strategy. From the original condition, only 9 students (23.68%) from 38 students could describe objects / people / certain places, in the first cycle there were 15 students (39.47%) who could describe certain objects more correctly. In the second cycle as many as 25 students (65.79%) can describe certain people more correctly. In the third cycle there is a decline in student learning outcomes. Only 20 students (52.63%) can describe a particular place more correctly. It can be concluded that PWIM is significant in improving student learning outcomes in learning English writing, especially in describing objects / people / specific places